Controlled growth of ZnO layers and nanowires using methane as reducing precursor. Issue 21 (25th July 2017) - Huber, Florian; Puchinger, Anouk; Ahmad, Waleed; Madel, Manfred; Bauer, Sebastian; Thonke, Klaus
Abstract: Abstract : Zinc oxide (ZnO) layers and nanowires were grown by chemical vapor deposition (CVD) using methane (CH4 ) as reducing agent. Compared to conventional CVD processes, which commonly use graphite powder to reduce the ZnO powder source material, this low-cost method allows an improved controllability of the growth processes. Specifically, the consumption of the source material–a commercially available ZnO powder–can be controlled in a very precise way by varying the flow of the reducing CH4 or the re-oxidizing O2 . Using this parameter, the growth can be switched between ZnO layers and nanostructures. High-quality ZnO layers have been grown on gallium nitride (GaN) substrates and on c -plane sapphire with an intermediate aluminum nitride (AlN) nucleation layer. By adjusting the growth conditions accordingly, ZnO nanowires were also grown with this method catalyst-free using a - and c -plane sapphire with ZnO nucleation layer as a substrate. The optical properties of the nanowires were investigated by low-temperature photoluminescence (PL) and compared to samples grown by conventional carbo-thermal CVD.